Modelling of dual-polarization interferometry in stellarators - Filippov, V.; Grekov, D.; Azarenkov, N. (Вопросы атомной науки и техники, 2019)
The dual polarization interferometers have been designed and applied in the Uragan-3M and Uragan-2M torsatrons. However, an extensive modeling of microwave propagation through the plasma in the sheared magnetic field should be provided for correct interpretation of data. For this purpose, the system of two bounded ordinary differential equations of the second order for the electric fields of the ordinary and extraordinary waves was solved numerically. The transfer matrix from launching to receiving waveguides was obtained in the wide range of plasma parameters. This gives the possibility to understand the results of already fulfilled measurements and to propose the optimized way for dual-polarization interferometry in stellarators. Двополяризаційні інтерферометри було застосовано в торсатронах Ураган-3М та Ураган-2М. Для коректної інтерпретації результатів експериментів, необхідно виконати моделювання поширення мікрохвиль, що зондують плазму, через плазму в магнітному полі змінного напрямку. З цією метою система двох пов’язаних диференційних рівнянь другого порядку для електричних полів звичайної та незвичайної хвиль розв’язувалась числовим методом. У широкому діапазоні параметрів плазми було отримано передаточну матрицю від рупора, що випромінює хвилі, до рупора, що їх приймає. Це дало можливість краще зрозуміти результати проведених експериментів і запропонувати оптимізовану схему двополяризаційного інтерферометра. Двухполяризационные интерферометры применялись на торсатронах Ураган-3М и Ураган-2М. Для корректной интерпретации результатов экспериментов необходимо промоделировать распространение зондирующих волн через плазму в магнитном поле переменного направления. Для этого система двух связанных дифференциальных уравнений второго порядка для электрических полей обыкновенной и необыкновенной волн решалась численно. В широком диапазоне параметров плазмы была получена передаточная матрица от излучающего рупора к приемному рупору. Это дало возможность лучше понять результаты проведенных экспериментов и предложить оптимизированную схему двухполяризационного интерферометра.